PENERAPAN MODEL PEMBELAJARAN INKUIRI DENGAN APLIKASI ZOOM DALAM MENINGKATKAN HASIL BELAJAR MATA KULIAH HUBUNGAN PUBLIK PADA MAHASISWA PRODI BAHASA INDONESIA - Putu Dessy Fridayanthi (Widyadari : Jurnal Pendidikan, 2021)
The purpose of this study was to determine whether there was a student response and the effect of the application of the inquiry learning model with the zoom application in increasing the understanding ability of the Public Relations course. This type of research is an online classroom action research through the zoom application. This action research was conducted at the PGRI Mahadewa University of Indonesia, which is located on Jl. Seroja 57 Tonja Denpasar, Bali. The subjects in this study were students of semester VII B of the Indonesian and Regional Language Education Study Program, PGRI Mahadewa Indonesia University in the odd semester of the 2020/2021 academic year, and the object of this research is a study of the public relations course and student responses to inquiry learning models carried out online. through virtual zoom. This study used two cycles, and each cycle went through four stages of the activity process (1) planning, (2) action, (3) observation, and (4) evaluation and reflection. Data collection techniques in this study are using test and observation methods. The results showed (1) the application of the inquiry learning model with the zoom application can improve the understanding of the Public Relations course. (2) There is a positive student response to the application of the inquiry learning model with the zoom application in increasing the ability to understand the Public Relations course.